Rare earth element and Pb isotope variations in a 52 kyr peat core from Lynch’s Crater (NE Queensland, Australia): Proxy development and application to paleoclimate in the Southern Hemisphere - Kylander, M.E.; Muller, J.; Wüst, R.A.J.; Gallagher, K.; Garcia-Sanchez, R.; Coles, B.J.; Weiss, D.J. (Geochimica et cosmochimica acta, 2007)
Accurate prediction of future climate scenarios is contingent on our understanding of past and present climate mechanisms. This is done in part through the reconstruction of historical climate changes using proxy records from terrestrial and marine archives. Terrestrial archives covering the Holocene and late Pleistocene are limited, most acutely in the Southern Hemisphere. Here, Rare earth elements (REE) and Pb isotopes are developed as inorganic geochemical proxies of mineral dust source changes and, by extension, climate change. Using a peat core from Lynch’s Crater in NE Queensland, Australia, we present the first long-term (c. 52 kyr) terrestrial record of atmospheric REE and Pb deposition (with the exception of four wet events which represent periods of erosion from the crater itself) in the Southern Hemisphere covering both glacial and interglacial times. Based on a combination of correlation analyses, Al and Ti normalised profiles and elemental patterns, we establish REE are immobile within the peat deposit and not subject to significant post depositional diagenetic changes (important particularly for Ce). This is vital as REE can be mobile under acid and organic rich conditions like those that can occur during the development of a peat deposit. The volcanic provinces of eastern Australia have characteristic Eu anomaly signatures, which allowed their use in a novel way to detect changes in dust source to Lynch’s Crater. Between 41,095 and 52,505 BP the deposit was under the influence of dust carried by long distance transport (>1500 km) from SE Australia. From 8525 to 40,815 BP regional sources (100–1500 km) dominated the deposited signals while between 1740 and 8390 BP the dust signal was controlled by local sources (<100 km). These findings were also confirmed by Pb isotope data. Changepoint modelling refined the timing of these changes in dust source, recognizing concurrent shifts in our tracing tools ((Eu/Eu ∗) PAAS and 206Pb/ 207Pb). These changepoints were then compared to other palaeoenvironmental records (pollen, lake levels and dune building) from eastern Australia and found to be similar. Our results demonstrate that REE and Pb isotopes are effective tools for tracing past changes in atmospheric dust sources and to the study of climate change using minerotrophic peat deposits.